2018
DOI: 10.1016/j.omtn.2018.06.006
|View full text |Cite|
|
Sign up to set email alerts
|

PAK1 Promotes the Proliferation and Inhibits Apoptosis of Human Spermatogonial Stem Cells via PDK1/KDR/ZNF367 and ERK1/2 and AKT Pathways

Abstract: Spermatogonial stem cells (SSCs) have significant applications in reproductive and regenerative medicine. However, nothing is known about genes in mediating human SSCs. Here we have explored for the first time the function and mechanism of P21-activated kinase 1 (PAK1) in regulating the proliferation and apoptosis of the human SSC line. PAK1 level was upregulated by epidermal growth factor (EGF), but not glial cell line-derived neurotrophic factor (GDNF) or fibroblast growth factor 2 (FGF2). PAK1 promoted prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 48 publications
2
32
1
Order By: Relevance
“…Wang et al found that overexpression of PAK1 promoted cell proliferation in cutaneous T-cell lymphoma via suppression of PUMA and p21 [34]. Fu et al found that PAK1 promoted the proliferation and inhibited apoptosis of human spermatogonial stem cells via PDK1/KDR/ZNF367 and ERK1/2 and AKT pathways [30]. However, in the present study, we found that up-regulation of PAK1 by IL-1β inhibited proliferation of chondrocytes.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Wang et al found that overexpression of PAK1 promoted cell proliferation in cutaneous T-cell lymphoma via suppression of PUMA and p21 [34]. Fu et al found that PAK1 promoted the proliferation and inhibited apoptosis of human spermatogonial stem cells via PDK1/KDR/ZNF367 and ERK1/2 and AKT pathways [30]. However, in the present study, we found that up-regulation of PAK1 by IL-1β inhibited proliferation of chondrocytes.…”
Section: Discussioncontrasting
confidence: 81%
“…PAK1 is widely distributed in the human body, which has been shown to interact with nicotinamide adenine dinucleotide phosphate (NADPH) oxidase in multiple cell types [10]. Previous studies showed that PAK1 was involved in the regulation of NADPH oxidase in diseases associated with inflammatory activation, proliferation and angiogenesis of endothelial cells [29,30]. In addition, PAK1 was also confirmed to control mitogen-activated protein kinase (MAPK), such as c-Jun N-terminal kinase (JNK) and p38 MAP kinases, and NF-κB activity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Pak1 promotes the proliferation and inhibits apoptosis via the Akt pathway. 35) Similarly, silencing of Pak1 significantly decreased the phosphorylation of Akt and deactivated Akt signaling pathway. Given that miR-665 inhibitor could significantly depress the accumulation of ROS and cell apoptosis by promoting the phosphorylation of Akt, silencing of Pak1 could inhibit the protection of miR-665 inhibitor and depress the phosphorylation of Akt in H/Rtreated H9c2 cells.…”
Section: Discussionmentioning
confidence: 95%
“…To identify the targets of PAK1, miRNA microarrays were performed to compare the global miRNA-expression patterns between PAK1 knockdown and the control siRNA. We utilized three pairs of small interfering RNAs (siRNAs) targeting different regions of PAK1 mRNA, and we found that the interfering effect of PAK1-siRNA2 is the most prominent 24 . Total RNA was extracted from human SSCs at 24 hr after PAK1-siRNA2 and control siRNA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, very little is known about the role of genetic and epigenetic factors in controlling human spermatogenesis and male infertility. We have recently demonstrated that PAK1 is regulated by epidermal growth factor (EGF) and that PAK1 promotes the proliferation and decreases apoptosis of human SSCs through PDK1-KDR-ZNF367 and ERK1/2-AKT 24 . Notably, low levels of PAK1 may be associated with NOA patients 24 .…”
Section: Discussionmentioning
confidence: 99%